TEACHERS' PERCEPTIONS ON THE MODEL DEVELOPMENT OF CHARACTER BASED TEACHING MATERIAL FOR SMA/ MA STUDENTS IN SEMARANG - Suwandi Suwandi; Sukma Nur Ardini (Soegijapranata Catholic University, 2015)
This study was conducted with the objectives of finding out whether or not the teaching material entitled